La danse étatsunienne du début du XXème siècle aux années 1980 : histoire d’une dichotomie entre mouvement et geste - Claudie Servian (Interfaces)
Movement is the essence of dance: the body contracts and releases, flexes and extends, gestures and moves. Since the beginning of the 20th century, North-American choreographers have emphasized either movement, the fact of bodily action, or gestures, movements to which something is added like meaning, function, connotation or intention. Influenced by Delsarte’s theories on the link between movements and psychological behaviour, Isadora Duncan is convinced that dance is a more effective medium than language in revealing desires and feelings. Dance gestures alone have the capability to communicate affectively. Similarly, Martha Graham thinks that movement never lies. For modern dancers, dance is human thought and emotions performed by the human body for human purposes. Merce Cunningham claims that the purpose of his dances is movement for movement. When movement is the focus, dance can be considered as a semi-autonomous system. Meaning is then found in the structural manipulation of the elements of space, time, rhythm, dynamics, and the body’s physical control. For postmodern dancers, the purpose of dance is primarily movement, the creation of an ephemeral design in which concept (ideas about dance), process which leads to performance, medium (the body instrument), and product (the dance performance) merge. In this case, attention then focuses more on the formal qualities of dance.